SOSIALISASI PENINGKATAN DAYA SAING UMKM OLAHAN KERIPIK SINGKONG RASA GURIH PEDAS MELALUI KEMASAN DAN DIGITAL MARKETING MBKM PROGRAM KKN TEMATIK DI DESA PETANANG - Nauly, Akta Dia; Pebianti, Alpina; Cahyani, Mitha; Hertati, Lesi; Hendarmin, Rum; Syafri, Lili; Munandar, Aris (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
One of the problems that makes the competitiveness of MSMEs is still low is the limited ability of business actors in doing marketing. This community service activity is carried out to introduce cassava chips MSME products to a wider market, increase MSME competitiveness through the use of digital marketing. In this service, the method used to solve problems is to provide counseling, training, and assistance to MSME actors who become partners. This activity was carried out in stages over 2 months. From the activities that have been carried out, partners understand enough about the concept of digital marketing and are able to use the internet to do marketing. The increased ability of partners in marketing is expected to help partners to gain a wider market and increase the competitiveness of partners as MSME actors.